PENGEMBANGAN SISTEM REPOSITORI ARSIP DIGITAL PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENDUKUNG SMART GOVERNANCE - Gunaidi, Aang; Nurhadryani, Yani; Muljono, Pudji (BACA: Jurnal Dokumentasi dan Informasi, 2025)
This research aims to analyze of archive process and to create prototype of digital archive repository system which can give easy in retrieval archive process. The method used in systems development using the prototyping model cosists of communication, quick plan, modeling quick design, construction of prototype, deployment delivery and feedback. The results show that the business process of archiving in Department of Population and Civil Registration of DKI Jakarta Province covers the creation, dissemination, arrangement, filing, retention, and reporting. The development of digital archive repository system in Department of Population and Civil Registration of DKI Jakarta Province was successfully done by prototyping method as iteration twice. The main function of this system is the processing of digital archives, export/import, archive circulation, archive retrieval system, and archive data reporting. This system has changed business processes that were previously done manually into digital. Test results distributed to 10 respondents that average value show that the system is made good and useful for users.